John N. Muafangejo, 1943-1987 : a perspective on his lino-cuts with special reference to the University of Bophuthatswana Print Collection - Cole, Collin (Rhodes University, Faculty of Humanities, Department of Fine Art, 1994)
By way of an analysis of the lino-cuts executed by Muafangejo, firstly elements and influences that are evident in terms associated with his works, will be traced, for example 'primitive' and 'traditional' elements. Secondly, the characteristics that are particular to this artist's work will be defined. It is believed that by using this avenue of approach, a clearer understanding of the artist's traditional world and possibly the stylistic placement of the artist can be attained. However, to rely only on historical and cultural influences to give a perspective of his work, will not be sufficient. It will only highlight a portion of the evidence needed to fully understand his work. (From the introduction).
Keywords: Muafangejo, John N., 1943-1987 -- Criticism and interpretation; Linoleum block-printing -- Art collections; Art,-- Namibian